Eucharist, the First Fruit and the Foundation of a Really Just Social Order. A Contribution on Occasion of the National Eucharistic Congress (Teología, 2016)
On occasion of the celebration of a National Eucharistic Congress, the author proposes to return to the original inspiration of those congresses, highlighting the social salvific dimension of the Eucharist facing the challenges presented by the argentine reality. One of these challenges is undoubtedly the establishment of a more just social order. As a contribution to this purpose, the article attempts to analyze the relationship between Eucharist and justice. This is done in five stages: a clarification of the concept of justice from the juridical-philosophical point of view and from the biblical perspective; a rereading of the biblical sources related to the sign and the meaning of Eucharist, where appears clearly why Eucharist has been considered the sacramentum caritatis; a speculative moment that seeks to explain the relationship between charity and justice, and its relationship with Eucharist; a verification of that interpretation in the Christian sacramental praxis of the first centuries; and finally, the recovery of some key texts of the Magisterium of the Church that have developed the theme. This leads to the conclusion that Eucharist expresses in an eminent way what it means to be a Christian, and, as consequence, why its celebration requires a specific ethical conduct. The Eucharist recalls that in Christ God’s justice was finally realized and a new order has been established; it expresses and encourages to establish a true “counterculture” in which justice and solidarity prevail; and it is the prophetic sign of the realization of the “new heavens and new earth”. Because of this, the meaning of the leitourgia of the People of God should be verified in its diakonia and martyria.
Keywords: Eucharist; Justice; Charity; Social Order; Christian Ethic